THE CORRELATION BETWEEN THE LEVEL OF KNOWLEDGE ABOUT DIABETES MELLITUS AND AGE FACTORS IN PANGA DISTRICT, ACEH JAYA REGENCY - Erna, Erna; Wahyuni, Srie; Nurdin, Ambia (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2023)
This study aims to conduct non-communicable disease surveillance with a focus on the relationship between the level of knowledge about diabetes mellitus and age level in Kuta Tuha Village, Panga District, Aceh Jaya Regency. Diabetes mellitus is one of the non-communicable diseases whose prevalence continues to increase in various regions, including in Indonesia. Adequate knowledge of the disease is essential for effective prevention and management. This study involved the entire population of Kuta Tuha Village consisting of 107 households, with the study period lasting for one month, from December 21, 2023 to January 10, 2024. Data were collected through a questionnaire designed to evaluate respondents' level of knowledge regarding diabetes mellitus and identify age as an important variable in understanding. The results of univariate analysis showed that the majority of respondents in this study were male (82.2%). The most common age group was 48-50 years old, which accounted for 50.5% of the total respondents. Despite previous socialization efforts regarding diabetes, there were still 17.8% of the population suffering from diabetes mellitus. It is recommended that health education programs be improved, with a more specific and sustainable approach, especially targeting the 48-50 years age group. This could include regular counseling, distribution of easy-to-understand educational materials, and establishment of support groups for people with diabetes and their families. Overall, this study provides important insights into the relationship between knowledge of diabetes mellitus and age, and emphasizes the importance of ongoing health education to improve public understanding of non-communicable diseases.